The Interpretation of Ecological Preservation in the Awig-awig (Customary Law) Text of Tenganan Pegringsingan Village: Positive Discourse Analysis - Astawa, I Gede; Budiarsa, Made; Mbete, Aron Meko; Simpen, I Wayan (e-Journal of Linguistics; Vol 13 No 1 (2019): e-jl-JanuaryDO - 10.24843/eJL.2019.v13.i02p06, 2019)
The earlier research on critical ecolinguistics tended to criticize the negative impacts of language in encouraging ecologically destructive behavior. However, this present study acts differently, it focusses on analysing positive impacts of language in preserving the environment. This present study aims at analysing the interpretation of ecological preservation revealed in the awig-awig (customary law) text belonging to Tenganan Pegringsingan Village.  The data of the research were taken from lexicons, phrases, clauses or sentences used in the written text of the awig-awig . The collected data were analysed using Positive Discourse Analyisi (PDA) developed by Stibbe (2017). The findings of the present study showed that the interpretation of ecological preservation in the awig-awig text took the form of preservation of natural ecology, preservation of human ecology, and preservation of spiritual ecology. The three findings above correspond to the Tri Hita Karana (THK) concept which was considered as the ecosophy of the study.